2017
DOI: 10.1590/1980-5373-mr-2016-0509
|View full text |Cite
|
Sign up to set email alerts
|

Fibers Obtained from Alginate, Chitosan and Hybrid Used in the Development of Scaffolds

Abstract: The main aim of this study was to develop scaffolds based on alginate, chitosan and hybrid fibers with and without glycerol. The scaffolds developed underwent assessments for tensile property, swelling ratio and weight loss, cellular viability, degradation and biomineralization, as well as DSC/TGA thermal analysis. Tenacity values showed that use of glycerol and the interaction between alginate and chitosan as a hybrid fiber were associated with increasing tenacity values. In the swelling and weight loss study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 27 publications
1
16
1
2
Order By: Relevance
“…In case of active agent loaded NCS, crystallization endotherm was registered at 158°C which was not very different from blank NCS. This observation confirmed that very low amount of active agent was present between alginate and chitosan layer (Furuya et al, 2017 ). Once alginate layer degraded at high temperature, it exposed more amorphous content (nisin and chitosan), which increased the temperature value for crystalline endotherm.…”
Section: Resultssupporting
confidence: 78%
“…In case of active agent loaded NCS, crystallization endotherm was registered at 158°C which was not very different from blank NCS. This observation confirmed that very low amount of active agent was present between alginate and chitosan layer (Furuya et al, 2017 ). Once alginate layer degraded at high temperature, it exposed more amorphous content (nisin and chitosan), which increased the temperature value for crystalline endotherm.…”
Section: Resultssupporting
confidence: 78%
“…The use of a coaxial flow in a non-microfluidic device allows for the production of fiber diameters that are comparable to those obtained in microfluidic devices (150–500 μm [27]), but with a processing speed that is one order of magnitude higher (0.5 mL/min versus 50 μL/min typically observed in microfluidic devices [27]). Furthermore, cohesive scaffolds are prepared within a very short time, for the benefit of cell survival, with a one-step procedure, avoiding the need for an additional step that is required to assemble discrete fibers that are produced in similar systems [24,37,38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Soluble protein concentration was determined by the colorimetric method of Bradford [36] which is based on the color change of the acidic solution of Coomassie Brilliant Blue G 250, when binding to a protein the maximum absorbance changes from 465 to 595 nm, and calculations were performed by Eq. 1 [5]: RP = Protein yield (%); P0 = Protein available for immobilization (mg), and Pads = (P 0 − P s − P f ) the amount of protein adsorbed to the support was determined as the difference between P 0 the proteins and remaining in the supernatant P s in the filtered and P f at the end of the immobilization process (mg).The yield of the immobilization process was calculated by Eq. 2:…”
Section: Bromelain Immobilizationmentioning
confidence: 99%
“…Heart valve rings, vascular grafts, percutaneous devices, and hernia repair meshes can be found. Also, the fibers have been used in regenerative medicine [4,5]. Use of fibers in bone tissue engineering offers clear advantages such as good porosity, lightness, and a better adjustable elastic modulus than a metallic product, which improves bone tissue regeneration [6].…”
Section: Introductionmentioning
confidence: 99%